Sialylated Receptor Setting Influences Mycoplasma pneumoniae Attachment and Gliding Motility. Issue 6 (30th September 2018) - Williams, Caitlin R.; Chen, Li; Driver, Ashley D.; Arnold, Edward A.; Sheppard, Edward S.; Locklin, Jason; Krause, Duncan C.
Summary: Mycoplasma pneumoniae is a common cause of human respiratory tract infections, including bronchitis and atypical pneumonia. M. pneumoniae binds glycoprotein receptors having terminal sialic acid residues via the P1 adhesin protein. Here, we explored the impact of sialic acid presentation on M. pneumoniae adherence and gliding on surfaces coated with sialylated glycoproteins, or chemically functionalized with α‐2, 3‐ and α‐2, 6‐sialyllactose ligated individually or in combination to a polymer scaffold in precisely controlled densities. In both models, gliding required a higher receptor density threshold than adherence, and receptor density influenced gliding frequency but not gliding speed. However, very high densities of α‐2, 3‐sialyllactose actually reduced gliding frequency over peak levels observed at lower densities. Both α‐2, 3‐ and α‐2, 6‐sialyllactose supported M. pneumoniae adherence, but gliding was only observed on the former. Finally, gliding on α‐2, 3‐sialyllactose was inhibited on surfaces also conjugated with α‐2, 6‐sialyllactose, suggesting that both moieties bind P1 despite the inability of the latter to support gliding. Our results indicate that the nature and density of host receptor moieties profoundly influences M. pneumoniae gliding, which could affect pathogenesis and infection outcome. Furthermore, precise functionalization of polymer scaffolds shows great promise for further analysis of sialic acid presentation and M. pneumoniae adherence and gliding. Abstract : We examined the influence of sialylated receptor environment on Mycoplasma pneumoniae adherence and gliding. M. pneumoniae attached to both α‐2, 3‐ and α‐2, 6‐sialyllactose but only glided on the former, and gliding was dependent on receptor density. Furthermore, as indicated by gliding tracks for M. pneumoniae cells attached to slides functionalized with 27% α‐2, 3‐sialyllactose and either no α‐2, 6‐sialyllactose (top) or 53% α‐2, 6‐sialyllactose (bottom), the presence of α‐2, 6‐sialyllactose reduced gliding frequency on α‐2, 3‐sialyllactose.